Arthroscopic treatment of early glenohumeral arthritis - Porcellini, Giuseppe (Springer International Publishing, 2012)
BACKGROUND: The articular cartilage of the shoulder is not endowed with intrinsic repair abilities, so the detection of chondral lesions during arthroscopy may indicate that additional articular procedures are needed. The aim of the current study was to evaluate the benefits of arthroscopy in patients with early shoulder arthritis, and to assess which clinical and radiological features are correlated with better arthroscopic outcomes. MATERIALS AND METHODS: Out of a total of 2,707 shoulders, 61 arthroscopies were performed on patients aged 30–55 years suffering from a painful early arthritic shoulder. We performed a retrospective study of 47 of those 61 patients with osteoarthritis at Samilson–Prieto stage I or II. SST and Constant score were used as outcome measures. Arthroscopic circumferential capsulotomy was performed to release the soft tissues and increase the joint space. Glenoid chondral lesions were caregorized according to location (anterior, posterior, centered) and size (small, large, total) and treated with microfractures; in the last 11 patients, we placed a engineered hyaluronic acid membrane, Hyalograft(®) C, on the surface of the glenoid. Postoperative care included mobilization the day after surgery, with the arm protected in a sling for two weeks. Follow-up examinations were performed at 3, 6, 12, and 24 months after surgery. The clinical and radiographic data collected were compared with those obtained at the last examination. RESULTS: The mean Constant score increased from 43.8 points to 79.1, and the mean SST score increased from 4.9 points to 9.4 points. Clinical outcomes improved significantly in 44 patients (93.6 %). The three patients (6.4 %) with the lowest scores showed progression of arthritis. Age, gender, glenohumeral distance, and presence of engineered hyaluronic acid membrane were not related to clinical scores. Recovery of range of motion as well as small and centered cartilage lesions were statistically associated with improved outcome. CONCLUSION: The main finding was that soft tissue procedures (including capsulotomy and synovectomy) associated with glenoid microfractures are only suitable for patients with early arthritis and preserved humeral head shape, particularly in cases with small and centered glenoid cartilage lesions.